Faktor-faktor yang mempengaruhi penerimaan bioteknologi oleh masyarakat Malaysia - Latifah Amin & Jamaluddin Md. Jahi, (Universiti Kebangsaan Malaysia, 2005)
Modern biotechnology has been viewed by many scientists and observers as the frontier of the 21st century revolution. Biotechnology has been identified as one of the five core technologies that will accelerate Malaysia’s transformation into a highly industrialized nation by 2020. Under the 8th Malaysian Plan, the government has allocated an amount of RM100 million for research and development in the biotechnology sector focusing on agriculture, health, environmental management and energy. Although biotechnology has huge potential in many sectors but it has been the object of an intense and divisive debate among the scientists, industries, governmental bodies involved in biotechnology regulation, NGOs and the public in advanced countries. Whether they like it or not, the Malaysian public will also be facing the same dilemma whether to accept and use biotechnology products or vice versa. Public awareness, perception and attitude towards biotechnology and products are important determinants of public support and acceptance. This paper will try to identify several biotechnology issues that may serve as challengers to the Malaysian public acceptance